Mapping and predicting a candidate gene for flesh color in watermelon - Chao-nan WANG; Fei-shi LUAN; Hong-yu LIU; Angela R. DAVIS; Qi-an ZHANG; Zu-yun DAI; Shi LIU (Journal of Integrative Agriculture, 2021)
The color of watermelon flesh is an important trait determined by a series of carotenoids. Herein, we used Cream of Saskatchewan (pale yellow flesh) and PI 186490 (white flesh) as parental materials for an F2 segregation and initial mapping using the bulked segregant analysis sequencing (BSA-seq) strategy. The BSA results revealed a flesh color-related QTL that spans approximately 2.45 Mb on chromosome 6. This region was preliminarily positioned in a 382-kb segment, and then narrowed down into a 66.8-kb segment with 1260 F2 individuals. A total of nine candidate genes were in the fine mapping interval, but only Cla007528 (encoding chlorophyllase) had non-synonymous mutations and was significantly expressed between the parental materials throughout flesh development. We also checked the expression patterns of the carotenoid metabolic pathway genes based on RNA-seq data and qRT-PCR validation. Three genes in the xanthophyll cycle (CICHYB, CINCED-1 and CINCED-7) exhibited differential expression patterns between the two parental lines at different flesh color formation stages. ClPSY1, CIPDS, CIZDS, CICHXE, CICRTISO and CILCYB also exhibited clearly different expression patterns accompanied by carotenoid accumulation.